Pengaruh Media Leaflet Terhadap Pengetahuan Dan Sikap Tugas Pengawas Menelan Obat (PMO) Tuberkulosis Di Puskesmas Bara-Baraya Kota Makassar - Clarisa Febrianti; Reza Aril Ahri; Andi Surahman Batara (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Based on data released by the Ministry of Health, the number of TB cases in 2019 in Indonesia was 203,100,000 people. The number of tuberculosis cases found was 543,874, and South Sulawesi Province was in eighth place with 19,568 cases. The number of TB cases shows that South Sulawesi Province has a fairly high number of TB cases. This study aimed to determine whether leaflet media influenced the knowledge and attitudes of tuberculosis drug swallowing supervisors at the Bara-Baraya Makassar Health Center, Makassar City. This type of quantitative research uses a quasi-experimental design with a one-group pre-post test design. The population was 41 respondents by determining the sample using the total sampling method and the tool used for data collection was a questionnaire. The analysis method includes univariate and bivariate analysis using the Wilcoxon test. The results of the study on the influence of leaflet media on knowledge and attitudes about the Duties of Tuberculosis Drug Swallowing Supervisors obtained p value = 0.000 <a = 0.05, which means that there is an influence of leaflet media on knowledge and attitudes about the Duties of Tuberculosis Drug Swallowing Supervisors at the Bara-Baraya Makassar Health Center, Makassar City. From the results of this study, the researcher hopes that leaflet media can be used as a more effective medium in conveying health information so that it can improve knowledge and attitudes about the duties of drug swallowing supervisors about Tuberculosis.